Simple and rapid liquid chromatography method for simultaneous determination of isoniazid and pyrazinamide in plasma (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: Treatment of tuberculosis (TB) requires a combination of drugs. Isoniazid (INH) and pyrazinamide (PZA) are key components of the fi rst-line regimen used in the treatment of TB and monitoring these drug levels in plasma would help in better patient care. The objective of the study is to develop and validate a simple and rapid high performance liquid chromatographic method for simultaneous determination of INH and PZA in human plasma. Methodology: The method involved deproteinisation of plasma with para hydroxy benzaldehyde and trifl uoroacetic acid and analysis using a reversed-phase C8 column and UV detection at 267nm. The fl ow rate was set at 1.5 ml/min at ambient temperature. The accuracy, linearity, precision, specifi city, stability and recovery of the method were evaluated. The method was applied to estimate plasma INH and PZA collected from six children with TB. Results: Well resolved peaks of PZA and INH at retention times of 3.2 and 6.1 minutes respectively were obtained. The assay was linear from 0.25 - 10.0 ìg/ml for INH and 1.25 – 50.0 ìg/ml for PZA. The within-day and between-day relative standard deviation for standards were below 10%. The average recoveries of INH and PZA from plasma were 104 and 102% respectively. Conclusions: A rapid and accurate method for simultaneous determination of INH and PZA in plasma was validated. The assay spans the concentration range of clinical interest. The easy sample preparation and small sample size makes this assay highly suitable for pharmacokinetic studies of INH and PZA in TB patients. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS 2012; IX (1) 13-18 DOI: http://dx.doi.org/10.3126/saarctb.v9i1.6960